2008
DOI: 10.1136/emj.2007.051292
|View full text |Cite
|
Sign up to set email alerts
|

Serum ischaemia-modified albumin increases in critical lower limb ischaemia

Abstract: There is a significant increase in serum IMA in limb ischaemia. Furthermore, using a cutoff of 0.22 ABSU, ROC curve analysis shows that IMA is 81.8% sensitive and 81.8% specific 81.8% in patients with clinically severe lower limb ischaemia. Future studies would be needed to determine if IMA would be clinically useful in the diagnosis of subtle limb ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 13 publications
1
20
1
Order By: Relevance
“…Modifications that alter the binding capacity of albumin for cobalt may arise during ischemiareperfusion as a result of acidosis, reduced oxygen tension, and the generation of free radicals. Recent research has shown that a variety of conditions may raise ischemia-modified albumin levels, including pulmonary embolism, mesenteric ischemia, peripheral arterial occlusion, deep venous thrombosis, and stroke, and that ischemia-modified albumin may be a diagnostic biomarker for these conditions (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Modifications that alter the binding capacity of albumin for cobalt may arise during ischemiareperfusion as a result of acidosis, reduced oxygen tension, and the generation of free radicals. Recent research has shown that a variety of conditions may raise ischemia-modified albumin levels, including pulmonary embolism, mesenteric ischemia, peripheral arterial occlusion, deep venous thrombosis, and stroke, and that ischemia-modified albumin may be a diagnostic biomarker for these conditions (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Recently, significant increases in IMA levels have been reported in various ischemic conditions, such as pulmonary infarct, critical lower limb ischemia and cerebrovascular disease, suggesting that IMA may be useful as a diagnostic marker for these conditions [6][7][8] . IMA has been shown to be elevated in patients after percutaneous coronary intervention as a result of ischemia-reperfusion injury [9] .…”
mentioning
confidence: 99%
“…Serum IMA is elevated in cardiac ischaemia,9 10 ischaemic stroke,11 bowel infarction12 and limb ischaemia 13. IMA levels were also found to be higher in case-control studies of DVT14 and PE15 patients in the ED.…”
Section: Introductionmentioning
confidence: 92%